Alteration of tubuliform silk gland cytoarchitecture with the reproductive cycle of the Western black widow spider, Latrodectus hesperus. Issue 4 (20th November 2015) - Herrera, Elizabeth; Nguyen, Ly Truc; Escobar, Erica; Ouriel, Wendy; Casem, Merri Lynn
Abstract: The protein synthetic and secretory activity of spider tubuliform glands is known to be coordinated with the reproductive stage of the spider. For spiders that produce multiple egg cases, such as the black widow Latrodectus hesperus, this means that the cells that make up the tubuliform gland cycle from minimal to maximal silk protein synthesis and exocytosis as the spider transitions from early vitellogenesis to a gravid state and back. The impact of these transitions on the cells that form the tubuliform gland has yet to be characterized. The entire tubuliform gland undergoes an elastic deformation, doubling in size in response to the accumulation and depletion of egg case silk proteins within its lumen. Similarly, the diversity and organization of organelles within the cytoplasm of the secretory epithelial cells that make up the wall of the tubuliform gland change with the reproductive stage of the spider. Progression of a spider from early to late vitellogenesis is accompanied by decondensed nucleoli and distention of the rough endoplasmic reticulum, markers of protein synthetic activity. The presumed silk proteins that fill the lumen of the tubuliform gland of a gravid spider include a fibrous matrix with homogeneous spherical inclusions. These components are also present within the cytoplasm of the cell; however, only the fibrous material appears to be enclosed by membranous organelles. Transition of the tubuliform gland from peak silk synthesis back to a quiescent state is marked by the appearance of multivesicular bodies and organelles resembling phagophores and autophagosomes, suggestive of a role for autophagy in the process of recovery. The reproducible cellular dynamics of the tubuliform silk gland of the black widow spider makes it a potential model system for study of the regulation of silk gene expression, endomembrane transport, and exocytosis of silk proteins and autophagy.